THE IMPACT OF FAMILY SOCIO-ECONOMIC CONDITIONS, LEARNING SPIRIT, AND ONLINE LEARNING SYSTEMS ON STUDENTS' LEARNING ACHIEVEMENT DURING THE COVID-19 PANDEMIC IN CLASS XI IN ECONOMICS - Masruchatin, Masruchatin (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2024)
This study aims to determine the significance of the influence of family socio-economic conditions, enthusiasm for learning, online learning systems on student achievement in class XI SMAN 4 Kediri in economics during the Covid 19 pandemic. This study uses multiple regression analysis to find the magnitude of significance partially and simultaneously. This research method is a survey method with a sample of 136 students. The technique used in data collection is a questionnaire technique (questionnaire) and documentation. The conclusions obtained from the results of the study are as follows: 1) The socio-economic condition of the family has a positive and partially significant effect on the learning achievement of class XI students of SMAN 4 Kediri in economics subjects during the covid 19 pandemic. The null hypothesis is rejected because the t-count value is greater than the t-table value (5.900 > 1.287), and a significance value of 0.000 is less than 0.05 (0.000 <0.05). 2) The enthusiasm for learning has a partial positive and significant effect on the learning achievement of class XI students at SMAN 4 Kediri in economics during the Covid 19 pandemic. The null hypothesis is rejected because the t-count value is greater than the t-table value (2.816 > 1.287), and a significance value obtained of 0.006 is smaller than 0.05 (0.006 <0.05). 3) Online system learning has a positive and partially significant effect on student achievement in class XI SMAN 4 Kediri in economics during the Covid 19 pandemic. The null hypothesis is rejected because the t-count value is greater than the t-table value (3.471 > 1.287), and a significance value of 0.001 is less than 0.05 (0.001 <0.05). 4) There is a simultaneous effect of family socio-economic conditions, enthusiasm for learning, online system learning on student achievement in class XI SMAN 4 Kediri in economics subjects during the covid 19 pandemic. The null hypothesis of the study was rejected because f-count > f-table (39,727 > 2.72) and a significance value of less than 0.05 (0.000 <0.05).